Oral energy supplementation improves nutritional status in hemodialysis patients with protein–energy wasting: A pilot study - Qin, Aiya; Tan, Jiaxing; Hu, Wen; Liu, Yuan; Chen, Lin; Tang, Yi; Qin, Wei (Frontiers in Pharmacology, 2022)
Background: Protein–energy wasting (PEW) is highly prevalent in hemodialysis (HD) patients, which is associated with poor quality of life, complications, and an increased risk of mortality. A prospective study in HD patients with 2 months of oral energy supplements (OESs) was performed. Methods: A total of 37 HD patients with PEW were finally enrolled in this prospective study and were randomized into the OES group (n = 19), which received oral energy supplementation (300 kcal) and dietary recommendations, while patients in the non-OES group (n = 18) received only dietary recommendations. The study duration was 2 months. The nutritional status of the patients was evaluated by laboratory indexes, body composition parameters, and the modified quantitative subjective global assessment (MQSGA) and malnutrition-inflammation score (MIS). Quality of life was evaluated by the Short Form Health Survey Questionnaire (SF-36). Results: After 2 months of therapy, a significant increase in serum albumin [39.6 (37.6–45.8) vs. 43.4 (39.1–46.7) g/L; p = 0.018], hemoglobin (101.0 ± 13.6 g/L vs. 111.8 ± 11.7 g/L; p = 0.042), and dietary energy intake (29.17 ± 3.22 kcal/kg/day vs. 33.60 ± 2.72 kcal/kg/day, p < 0.001) was observed in the comparisons of baseline in the OES group. Moreover, the OES group demonstrated significant amelioration in MQSGA [9 (8–13) vs. 8 (7–12), p < 0.001] and MIS [5 (3–10) vs. 3 (2–8), p < 0.001], physical functioning (p < 0.001), and mental health (p = 0.046) subsections of SF-36 compared with the baseline. No electrolyte disorders or dyslipidemia were observed in the OES group. Conclusion: OES in HD patients with PEW can significantly ameliorate energy supply, nutritional status, anemia, and quality of life.